The Finnish experience on maintaining a currency band in the 1980s - Jarmo Kontulainen; Olli-Pekka Lehmussaari; Antti Suvanto (Bank of Finland, 1990)
The paper reviews the Finnish experience of maintaining an explicit currency band since its creation in 1977. The emphasis is on the latter half of the 1980s, which is a period of free capital movements and unregulated domestic money markets. The first part of the paper gives an historical account of the past experience. It is seen that the band arrangement has given some, albeit limited, freedom to monetary policy. This is reflected in a higher interest rate differential than what would have been necessary in order to keep the exchange rate completely fixed and private capital movements on balance on the average. The second part presents a brief review to theoretical models of currency bands. In the third part the predictions of these models, as regards the relationship between the interest rate differential and the exchange rate, the perceived devaluation risk and the credibility of the band, are tested with the Finnish data from 1987 onwards. According to the results the interest rate differential and the exchange rate exhibit negative correlation, except for the periods of currency unrest. The term structure of the interest rate differentials, however, does not behave in the manner predicted by the theory. The perceived devaluation risk is positive, which does not, however, imply that the band itself would have been uncredible. The tests indicate that the band has been credible up to a twelve-month horizon, but not in a five-year horizon.
URN:NBN:fi:bof-201908061352
Keywords: 330